A retrospective study of traumatic injuries to teeth at a Nigerian tertiary hospital (2011)
Background: Various aspects of dental trauma have been studied worldwide. Most of these were among children and adolescents. However, studies involving the adult population with traumatized anterior teeth are few. Objectives: The objectives of this study were to report the pattern of trauma to anterior and posterior teeth among the late adolescent and adult patients seen at the Dental Centre, University College Hospital, Ibadan, Nigeria, the time lapse between trauma and patient presentation, reasons for dental consultation, and the type of treatment received. Materials and Methods: Data were extracted from the dental records of 146 patients with dental trauma that presented between May 2001 and June 2006. Results: One hundred and forty six patients were studied (87 males, 59 females) Males sustained injury more than females. The highest occurrence of trauma was in the age group of 25-34 years and least in the >65 years. Falls accounted for 34.3% of causes followed by RTA (19.2%). Enamel-dentine fracture was the most common type of injury, seen in 73 (38.6%) of the traumatized teeth, 5 were avulsed and 20 posterior teeth had cuspal fracture. All the cases of avulsion and most (83.3%) of root fracture presented within 1 week of injury while teeth that presented late had pulpal necrosis. 22% of the patients presented within 1 week of injury while 13.7% came after 10 years. Conclusion: There was late patients’ presentation with average duration of trauma before presentation being 4.6 years; however the more severe the outcome of trauma, the earlier the presentation. Poor esthetics followed by pain were the main complaints at presentation.